Chancery reform and law reform - Getzler, J (Cambridge University Press, 2011)
Michael Lobban shows how dissatisfaction with the law-equity split in English civil justice predated the Judicature Act reforms by two generations at least (one could argue two-and-a half centuries or more—periodization fails quickly). Lobban links the first modern debates over fusion to high legal politics on the one hand and to the more intricate internal problems of evidence, procedure, and jurisdiction on the other. Lawyers of the earlier Victorian age found the Chancery system bequeathed to them by Lord Eldon to be intolerable on two counts: it represented Old Corruption or monopolistic private control of public offices and it exacted heavy costs in procedural inconvenience, cost, and delay. Lobban does not see ideology such as Benthamite philosophy driving the rationalization of Chancery doctrine and institutions though he does not dismiss this factor entirely.